Model of Radio Managing System for Electro Vehicles’ Accumulators Wireless Feeding (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This article refers to studying of the system for wireless feeding of electro vehicles’ accumulators, and the description of it’s applicable efficiency. Preliminary design of the radio managing system is done. The electro vehicle feeding system is calculated for the freeway. By using LabVIEW program package model of radio managing system was designed.